Traffic lights system using microcontroller - P. , Nagendrareddy; R. , Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Since the past year’s we have been using traffic lights by the microcontroller. Several stoplights, in contrast to foreign countries, will be using traffic lights. The information will offer a forecasted route to the user by contacting totally different traffic lights on the method of the user. The location of this analysis with efficiency and to save a lot of time, which helps people to move to there place in a safe manner.